Erasmus Mobility Impact on Professional Training and Personal Development of Students Beneficiaries. (2nd June 2015) - Dolga, L.; Filipescu, H.; Popescu-Mitroi, M.M.; Mazilescu, C.A.
Abstract: The objective of this study is to analyze the participants' views on the impact of the Erasmus program on professional training and personal development of participants, highlighting the effects of the Erasmus mobility on student participants (educational level, professional, cultural, interpersonal, etc.). The participants in this study were 89 students of technical universities participating in the Erasmus mobility. The research involved a survey based on a questionnaire centered on the educational/vocational impact, cultural impact, and the relational impact of the Erasmus mobility on the personal and professional development of students/beneficiaries. The results show that an Erasmus mobility stimulate the acquisition of a social and cultural capital, acquisitions hard to gain in an otherwise normal context of life.